2010
DOI: 10.1371/journal.pone.0015567
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorescence Reporter Model Defines “Tip-DCs” as the Cellular Source of Interferon β in Murine Listeriosis

Abstract: Production of type I interferons, consisting mainly of multiple IFNα subtypes and IFNβ, represents an essential part of the innate immune defense against invading pathogens. While in most situations, namely viral infections, this class of cytokines is indispensable for host survival they mediate a detrimental effect during infection with L. monocytogenes by rendering macrophages insensitive towards IFNγ signalling which leads to a lethal bacterial pathology in mice. Due to a lack of suitable analytic tools the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 48 publications
4
40
0
Order By: Relevance
“…6A). As in prior reports, serum IFN-β levels were quite low (40, 42). However, a consistent difference was seen between WT and C5aR1−/− mice.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…6A). As in prior reports, serum IFN-β levels were quite low (40, 42). However, a consistent difference was seen between WT and C5aR1−/− mice.…”
Section: Resultssupporting
confidence: 79%
“…There are two major types of type 1 IFN, IFN-α and IFN-β. In L. monocytogenes models IFN-α expression is partially dependent on IFN-β, and type 1 IFN expression peaks at 24 h (3840). At this time point both IFN-α and IFN-β were significantly elevated in the serum of C5aR1−/− mice (p ≤ 0.0004) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The main mechanism described to this harmful role relies on the induction of apoptosis, particularly of lymphocytes as well as macrophages (47,48). It has been shown, using IFN-b reporter mice, that Tip-DCs are an important source of IFN-b during Listeria infection (49) as are CD11b + DCs (50). This finding might suggest that type I IFN production can act as a mechanism of selfregulation by immune cells, which could be subverted by Listeria for its own profit.…”
Section: Discussionmentioning
confidence: 99%
“…We found that stimulation of pDC with infected cells resulted in another distribution of IFN-a6 + , IFN-b + , and IFN-a6 + IFN-b + cell subsets than observed after stimulation with free virus. Previously, IFN-b + cells were phenotypically described as a specialized subpopulation of TNF and inducible NO synthase-producing DCs (41). It will be a matter of future research to determine markers that qualify subsets of pDC and mDC to respond to virus stimulation and to mount IFN responses.…”
Section: Discussionmentioning
confidence: 99%